Viscous Dissipation Effects on MHD Natural Convection Flow Over a Sphere in the Presence of Heat Generation - Alam, Md. M. M.; Alim, M. A. A.; Chowdhury, Md. M. K. M. K. (Nonlinear Analysis: Modelling and Control, 2007)
In this paper, the viscous dissipation effects on magnetohydrodynamic natural convection flow over a sphere in the presence of heat generation have been described. The governing boundary layer equations are first transformed into a nondimensional form and the resulting nonlinear system of partial differential equations are then solved numerically using finite-difference method together with Keller-box scheme. The numerical results of the surface shear stress in terms of skin friction coefficient and the rate of heat transfer in terms of local Nusselt number, velocity as well as temperature profiles are shown graphically and tabular form for a selection of parameters set consisting of heat generation parameter Q, magnetic parameter M, viscous dissipation parameter N and the Prandlt number Pr.